2015
DOI: 10.1111/jwas.12173
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Small‐scale Commercial Aquaponics in Hawai‘i

Abstract: Aquaponics, the symbiotic integration of aquaculture and hydroponics, has been touted as a sustainable food production technology. While there is anecdotal evidence, there are only a few studies on the economics of commercial aquaponics. In this study, we collect economic and production information from three aquaponic farms to investigate the economic feasibility of an aquaponics industry in Hawaii. Based on the information supplied by the farms, we develop a model case to analyze (i) profitability, (ii) retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 3 publications
4
103
0
Order By: Relevance
“…Nowadays, consumer awareness of the health benefits of locally and organically produced products is on the rise [11,12] and consumers make more conscious decisions when buying food [13], especially in developed and industrial countries. Consumer acceptance and certification criteria are of special interest for the development of commercial-scale aquaponics systems.…”
Section: The State Of the Art Of Aquaponicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, consumer awareness of the health benefits of locally and organically produced products is on the rise [11,12] and consumers make more conscious decisions when buying food [13], especially in developed and industrial countries. Consumer acceptance and certification criteria are of special interest for the development of commercial-scale aquaponics systems.…”
Section: The State Of the Art Of Aquaponicsmentioning
confidence: 99%
“…Consumer acceptance and certification criteria are of special interest for the development of commercial-scale aquaponics systems. All available studies about aquaponics have focused mainly on surveying aquaponics producers [14] or analysing specific case studies of aquaponics production, mostly in the USA [15], or specific Canadian provinces such as Alberta [16], or states such as Puerto Rico [17] and Hawaii [13,18,19]. To the author's knowledge, a limited number of studies are available on consumers' acceptance of aquaponics products, with only three published so far-on consumers' acceptance of aquaponics products in Malaysia [20] and on the perception of aquaponics products in Romania [21] and Berlin [22].…”
Section: The State Of the Art Of Aquaponicsmentioning
confidence: 99%
“…If there was the rising of the feed price more than 109.96% or the rising of the feed price up to Rp16.00-167.00/kg, so the business had not been feasible to be conducted. The results of the sensitiviy analysis reported by Valenti et al (2011) showed a business would not be feasible to be conducted, if there was a decrease in the selling price of tilapia at a value of 44% and the rising of the artificial feed price at a value of 90%, while according to Tokunaga et al (2015) the rising of the artificial feed cost at a value of 1%, increased the operational cost at a value of 0.13%. Based on the results of the sensitivity analysis obtained in Table 6, so it could be concluded that the koi fish culture business at PPFF was sensitive to a change in survival and was not sensitive to a change in the feed price.…”
Section: Sensitivity Analysismentioning
confidence: 93%
“…A financial analysis in the culture of tilapia Oreochromis niloticus showed a net B/C value of 1.48 and an IRR of 95% (Afolabi et al, 2012), a net B/C of 1.05 and an IRR of 11% under normal conditions and if that got additional incentive funds resulted an increase in net B/C to be 3.97 and an IRR to be 29% (Sara et al, 2014). Tilapia reared in aquaponic system resulted an IRR of 7.36% with a sales proportion of 21% tilapia and 79% vegetables (Tokunaga et al, 2015).…”
Section: Investment Criteria Analysismentioning
confidence: 99%
“…A study conducted by Liang and Chien in 2013 suggested that increasing feeding frequency and extending photo period would increase fish and plant yield, and decrease water nitrogen and phosphorus accumulation ( Liang and Chien, 2013). It was also reported that the introduction of freshwater prawn to vegetable tilapia aquaponics increased system stability, diversity and yield (Sace and Fitzsimmons, 2013).There were a handful studies related to the cost and profit for commercial scale aquaponics (Bailey et al, 1997;Tokunaga et al, 2013;Bunyaviroch et al, 2013), but these studies were conducted in tropical area and without the consideration of harsh winter weather like the mid-west U.S. The study conducted by Bailey et al in 1997 was in the U.S. Virgin Islands, so neither greenhouse nor equipment designed to heat the greenhouse was considered in the analysis, and there were no supplemental lights, either.…”
mentioning
confidence: 99%